In Good Company The Fast Track from the Corporate World to Poverty, Chastity, and Obedience - S. J. Martin (Sheed & Ward, 2000)
The story of one young man's remarkable journey from corporate America to the Society of Jesus. James Martin leads you from his Catholic childhood through his success and ultimate dissatisfaction with the business world, to his novitiate and profession of vows as a Jesuit.